Arithmetic of the sound of silence - Robert Madoi Nasaba (Communicare)
The web 2.0 has revolutionised the way in which we communicate with the effect that marginalised groups, including women, can represent themselves – instead of being represented from another’s perspective. However, this article argues that the blur of mainstream media and web 2.0 allows men to assume a superior status to women – especially in the global South. The thesis of this article proffers a fresh insight that goes beyond the descriptions of how the web creates contraflows of information for Southern women. At the heart of the debate is the impact garnered – or rather lack of it – when user-generated content from the web 2.0 is used to counterbalance issues from a mainstream point of reference. Using two independent Ugandan media houses as case studies, the article explains data collected through participant observation and unstructured interviews. The article finds that while Southern women have managed to use online spaces (periphery) to acknowledge their sisterhood, an awareness of intersectionality in the mainstream (centre) is conspicuously absent. It draws on the feminist communication theory as informed by feminism and finds that men continue to be privileged when online (periphery) and offline (centre) communities are blurred. To address this, women will have to robustly participate in the news construction process at the “centre.”